Analysing instructors’ questions in ESL classroom / Jun Nirlawati Mohd Sahidol and Kamisah Ariffin - Mohd Sahidol, Jun Nirlawati; Ariffin, Kamisah (Universiti Teknologi MARA Cawangan Pahang, 2019)
In teaching, instructors have the responsibilities to ensure that the objectives of the lesson for that day are accomplished and that the students understand the lesson. One of the most effective ways to achieve this is by asking questions. Although most of the questions asked in the classroom are usually related to the pedagogical aspects of teaching and learning, questions can also serve different functions. This study identified the functions of questions in ESL classroom discourse in a public university. The data consisted of audio recording data of five ESL instructors. The data were transcribed and analysed based on the framework set for the investigation: the functions of questions, types of questions and speech act. The analysis revealed that the functions of these instructors’ questions were limited mainly to evoking students’ response and seeking information. The findings raise some legitimate concerns for the instructors’ limited use of questions in the classroom for effective teaching. Some recommendations are put forward for instructors to explore and enhance the use of different functions of questions in their teaching.